91 Redesigning specialist palliative and hospice care to meet the needs of people with frailty. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Nicholson, Caroline; George, Rob; Pace, Victor; Richardson, Heather
Abstract : Background: Older people with multimorbidities will dominate palliative care in coming decades. For them, dying can be slow and unpredictable. Care models integrated across the spectrum of geriatric and palliative medicine, health and social care, are emerging. We draw on current theory and evidence to develop a framework that assists current services attune to the needs of this population. Methods: We used stepped framework construction.Eight clinicians and service users reviewed and refined initial findings. to scope the palliative/geriatric literature and define focus, inclusion and exclusion criteria for a proactive palliative care model (Seymour 2014). Documents from 102 research, review, policy papers and grey literature were included. Face-validity testing extended to a wider consultation across care sectors, care commissioners and providers. Findings: Built around emergent concerns of recipient older people and their family as care partners, the framework identifies three intervention levels that work differently as clinicians; in partnership to improve services and the broader care system; as support to wider societal change. An optimal clinical response requires: Meticulous, systematic needs assessment using the right tools; Parallel planning across specialties for several possible outcomes; Sensitive discussions that are realistic about health conditions and age; Access to advanced palliative practice competent to stop as well as start treatments, and work across relevant specialties including rapid response in the community; Access to rehabilitative care that optimizes function; 'Watchful Waiting', where purposeful, low-level proactive engagement with people and families identifies incremental changes and responds appropriately; Effective, relevant bereavement care. Outcome: This Age Attuned Hospice framework offers a flexible structure for organisations seeking to become more responsive to the older, frail population whilst maintaining effective current specialist practice.